Fast, slow and reverse polymorph transformations in thin films of a 5,10-dihydroindolo[3,2-b]indole derivative - Herrmann, Niklas; Korychenska, Oleksandra; Ta, Ngoc Phi; Mayneord, Guy E.; Rodríguez-Martínez, Xabier; Toolan, Daniel T. W.; Robertson, Craig C.; Iraqi, Ahmed; Clark, Jenny; Zaumseil, Jana (Journal of materials chemistry. C, Materials for optical and electronic devices, 2025)
Many small-molecule organic semiconductors can crystallize in different polymorphs, which influences their electronic (charge transport) and optical (absorption and fluorescence) properties. Understanding polymorph formation and transformation is crucial to control these properties for potential applications. Here we explore different thin films of a newly synthesized derivative of 5,10-dihydroindolo[3,2-b]indole, which shows high photoluminescence quantum yields even in the solid state as well as hole transport. Deposition of this indoloindole-based p-type semiconductor by thermal evaporation and zone-casting from solution results in distinct film morphologies and a metastable polymorph that can transform into more stable polymorphs at room temperature over timescales from hours to months. Their conversion and changing structural, optical and electronic properties are characterized by grazing incidence wide-angle X-ray scattering (GIWAXS), atomic force microscopy (AFM), absorption, fluorescence, and Raman spectroscopy as well as charge transport measurements in field-effect transistors (FET). Rough and polycrystalline films result in very fast polymorph transformation, while defect-free and smooth zone-cast films are stable for several months. Annealing these films does not lead to faster conversion but instead to thermodynamic stabilisation of the metastable polymorph and thus even a reversal of aged thin films. For this and potentially other organic polymorphic systems, long-term retention of a metastable polymorph and its electronic and optical properties can be achieved by controlling the initial film morphology, while annealing can indeed induce the formation of metastable polymorphs.